Pengaruh Latihan Plyometric Hurdle Jump Terhadap Daya Ledak Otot Tungkai Bawah Pada Pemain Futsal di Karya Futsal Medan Tahun 2025 - Sontiar Lumbantoruan; Ira Manda sari Berampu; Santo Damerius Silitonga; Surya Syahputra Berampu; Timbul Siahaan; Imelda Derang (Jurnal Masyarakat Indonesia (Jumas), 2025)
Background: Futsal is now one of the most popular sports in the community. This can be seen from the existence of futsal courts in almost every region, whether they meet the standards or not. This achievement sport is well organized, has a planned program, and sets certain targets to reach the peak of achievement. One important component in the physical condition needed in the game of futsal is the explosive power (power) of the leg muscles. Explosive power is defined as the ability of a muscle to face resistance with a very fast contraction. This concept includes a combination of strength and speed of muscle contraction that is dynamic and explosive, where the muscle must release maximum strength in the fastest possible time. Objective: To determine the effect of giving Plyometric Hurdle Jump on lower limb muscle explosiveness in futsal players. Methods: This study uses an experimental type with a quasi-experimental approach pre test and post test design with one group. The sample of this study amounted to 15 people with meetings 2 times a week for 8 meetings. Results: normality test with Shapiro Wilk Test obtained data before and after not normally distributed p <0.05. Based on the analysis using the Wilcoxon test, the p-value = (0.002 <0.05) then Ha is accepted and H0 is rejected. Conclusion: there is an effect of Plyometric Hurdle Jump on the explosive power of the lower leg muscles of futsal players